2004
DOI: 10.1136/adc.2003.034249
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in habitual activity in children with cystic fibrosis

Abstract: Aims: (1) To compare habitual activity levels in prepubescent and pubescent boys and girls with different degrees of CF lung disease severity and healthy controls. (2) To assess the relation between habitual activity levels and measures of fitness, lung function, nutrition, pancreatic status, and quality of life. Methods and Results: A total of 148 children (75 girls and 73 boys) with CF and matched controls were studied. Regardless of disease severity, there were no differences in habitual activity between pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 33 publications
10
126
2
1
Order By: Relevance
“…11,23,24 In a qualitative study of youth with CF, Willis et al 16 reported that girls who did not adhere to treatment were more likely to experience guilt compared to boys. This self-reflection about guilt is consistent with adolescent girls' greater private selfconsciousness, 17 which may be associated with more treatment discouragement, lower self-esteem 11,25 and poorer mental health reported for girls.…”
Section: Introductionmentioning
confidence: 99%
“…11,23,24 In a qualitative study of youth with CF, Willis et al 16 reported that girls who did not adhere to treatment were more likely to experience guilt compared to boys. This self-reflection about guilt is consistent with adolescent girls' greater private selfconsciousness, 17 which may be associated with more treatment discouragement, lower self-esteem 11,25 and poorer mental health reported for girls.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the sex difference in habitual activities among people with CF is well described [33], this result suggests that patient preference also exerts a significant influence on the choice of airway clearance technique. In addition, people with CF who do not use any primary airway clearance technique had high % predicted FEV 1 (median 78%) and low total IV antibiotic-days (median 0), suggesting that these people may have felt well and therefore chose not to perform airway clearance.…”
Section: Baseline Characteristicsmentioning
confidence: 87%
“…It has been established, that aerobic and anaerobic capacity is reduced in most patients with CF when compared to their healthy counterparts, with impaired respiratory function and malnutrition being likely contributing factors (7)(8)(9)(10). It has also been documented that children with CF with higher activity levels have a better aerobic and anaerobic fitness and nutritional status, and a significantly lower disease severity (11). Moreover, higher aerobic fitness is associated with a higher health-related quality of life (11;12).…”
Section: Exercise Testing In Cystic Fibrosis (Cf) Is Gaining Clinicalmentioning
confidence: 99%
“…After a 12-week follow-up period, most outcome parameters decreased compared to pretraining levels, except of anaerobic performance and quality of life (13). Moreover, CF children with higher levels of habitual activity have been found to possess increased anaerobic power during the WAnT and quality of life (11). More research is required in this field, in particular using training studies, to provide more detailed recommendations for exercise programs.…”
Section: Maximal Exercise Testsmentioning
confidence: 99%